THE INFLUENCE OF JOB STRESS AND COMPENSATION TO JOB SATISFACTION AT PT. TRI MEGAH MAKMUR - R Sudiarditha, I Ketut; Baqi, Fikri Haikal; Handaru, Agung Wahyu (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
The purpose of this research are: 1 ) To know description and how picture level job stress, compensation and job satisfaction atPT Tri Megah Makmur. 2) To know the influence of job stress tojob satisfaction atPT Tri Megah Makmur. 3) To know the influence of compensation to job satisfaction atPT Tri Megah Makmur. 4) To know empirically the influence of job stress and compensation tojob satisfaction atPT Tri Megah Makmur. 5) To know how far the contribution of job stress and compensation tojob satisfaction atPT Tri Megah Makmur. This research is using descriptive and explanatory survey analysis. This research is taken to 70 sales employees atPT Tri Megah Makmur, While the data collection technique was carried out by spreading kuisioner, which are then processed using SPSS versi 21.00.The analysis shows that: 1) level of compensation and job satisfaction are on a lower level, while the job stress are high. 2)Job stress have negative effects and significantly on job satisfaction. 3) compensation havepositive effect and significantly on job satisfaction. 4) job stress and compensation significantly influence on job satisfaction. Keyword: Job Stress, Compensation, Job Satisfaction